2012
DOI: 10.2135/cropsci2011.09.0481
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs in Biomass and Nutrient Allocation in Prairies and Corn Managed for Bioenergy Production

Abstract: Prairie vegetation has the potential to serve as a bioenergy feedstock with favorable environmental impacts but generally yields less than corn (Zea mays L.). To more fully assess the potential of prairie vegetation to serve as a biofuel feedstock, more needs to be understood about prairie responses to different management strategies, including fertilization. We hypothesized that (i) N fertilization would increase prairie productivity and nutrient content and (ii) fertilized prairie would produce similar amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 50 publications
(78 reference statements)
4
41
3
Order By: Relevance
“…Our findings also contrast with at least one in situ study; Jarchow and Liebman (2012) reported greater root biomass of C 4 grasses in unfertilized systems compared with their fertilized system. Our findings also contrast with at least one in situ study; Jarchow and Liebman (2012) reported greater root biomass of C 4 grasses in unfertilized systems compared with their fertilized system.…”
Section: Root and Biomass Allocation Responses To Added Nitrogencontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings also contrast with at least one in situ study; Jarchow and Liebman (2012) reported greater root biomass of C 4 grasses in unfertilized systems compared with their fertilized system. Our findings also contrast with at least one in situ study; Jarchow and Liebman (2012) reported greater root biomass of C 4 grasses in unfertilized systems compared with their fertilized system.…”
Section: Root and Biomass Allocation Responses To Added Nitrogencontrasting
confidence: 99%
“…In annuals, Russell et al (2009) reported no change in corn (Zea mays L.) root biomass with increasing N additions, whereas Durieux et al (1994) reported a decrease in root mass with increasing N rates at corn harvest, especially in drier growing seasons. In a perennial system, Jarchow and Liebman (2012) found that inorganic N fertilizer additions significantly reduced root biomass in a perennial C 4 grass system. At the same site, Dietzel et al (2015) found that inorganic fertilizer significantly increased root biomass in a mixed prairie system.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Tilman et al, 2001Tilman et al, , 2006 has supported the theory that yield increased with diversity. However, other research has found yield of specific monocultures or simple mixtures often equals or exceeds highdiversity mixes (Jarchow and Liebman, 2012;Johnson et al, 2010;Picasso et al, 2008;Springer et al, 2001). In particular, mixtures that include a warm-season perennial grass (often switchgrass) and a high-yielding legume (such as alfalfa [Medicago sativa]) often yield more than monocultures of the same species or higherdiversity mixtures (DeHaan et al, 2010;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While leguminous forbs produce relatively little harvestable biomass, they may provide sufficient plant-available nitrogen to maintain high graminoid biomass yields in the absence of nitrogen fertilizer [43]. Grasses provide higher potential ethanol yields per unit biomass [21,44], but forbs offer greater energy content per unit biomass when the biomass is directly combusted or thermochemically converted to other fuels [44].…”
Section: Harvest Efficiency Is Greater In Graminoids Compared To Forbsmentioning
confidence: 99%